ANALISA HUBUNGAN BURNOUT DAN BEBAN KERJA PERAWAT DI RUMAH SAKIT PEKANBARU MEDICAL CENTER - Awaliyah Ulfah Ayudytha Ezdha; Abdurrahman Hamid (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Hospital is health service providers that have different characteristics from other organizations Nurses are the spearhead of whether or not the health services provided to patients. This is due to the dominant number (50-60% of all employee), and is tasked with caring for and looking after patients 24 hours a day. Burnout is a prolonged response related to factors that cause stress that constantly occurs at work where the result is a combination of workers and work. Nurse fatigue occurs when nurses work more than 80% of their work time. The purpose of this study was to determine the relationship of burnout between nurses and workload in Pekanbaru Medical Center Hospital. The method of this study was descriptive correlation with cross sectional approach conducted on 35 respondents. The sampling technique uses total sampling. The analysis used is univariate analysis and bivariate analysis using Chi-square test. The results showed a significant relationship between burnout and workload (p = 0.024). Based on these results, the researchers recommend that the management of the Pekanbaru Medical Center Hospital pay more attention to the nurse's workload by calculating the nurse's workload so that the nurse's burnout rate can be avoided because it can relantionship with the nurse's performance plays an important role in patient care